2019
DOI: 10.3748/wjg.v25.i30.4261
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, localization, and types of gastrointestinal stromal tumor-associated neoplasia

Abstract: BACKGROUND In recent years, increasing evidence of second neoplasms associated with gastrointestinal stromal tumors (GIST) has been found. Numerous case reports, mostly retrospective studies and a few reviews, have been published. To our knowledge, however, no systematic review or meta-analysis of the existing data has been performed so far. AIM To prepare a compilation, as complete as possible, of all reported second tumor entities that have been described in associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 133 publications
1
23
0
3
Order By: Relevance
“…GIST-associated sarcomas are rarely reported in the literature considering that soft tissue tumors comprise only 0.5–3% of all GIST-associated neoplasms [ 12 , 14 ]. Cases of synchronous, GIST-associated sarcomas are even less frequently reported and they are usually liposarcomas [ 27 ], angiosarcomas [ 28 ], angiomyoliposarcomas [ 24 ], and leiomyosarcomas [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GIST-associated sarcomas are rarely reported in the literature considering that soft tissue tumors comprise only 0.5–3% of all GIST-associated neoplasms [ 12 , 14 ]. Cases of synchronous, GIST-associated sarcomas are even less frequently reported and they are usually liposarcomas [ 27 ], angiosarcomas [ 28 ], angiomyoliposarcomas [ 24 ], and leiomyosarcomas [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the rate of a second malignancy in GIST patients is higher than expected. GISTs with synchronous malignancy of the GI tract are described as ranging from 10% to 35%, with the majority of them being adenocarcinomas [ 1 , 9 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…GIST are considered to develop from interstitial cells of Cajal (ICC), which play an important role in autonomous gastrointestinal movement. The most common localization of GIST is the stomach, followed by other gastrointestinal tract localizations [ 1 ]. GISTs of the stomach presenting as an intratumoral abscess are extremely rare, which necessitates emergency surgery, we report a case of a stomach GIST developing an intratumoral abscess, in whom emergency surgery was performed.…”
Section: Introductionmentioning
confidence: 99%
“…There are publications in the literature showing that the association is mostly synchronous [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Synchronous associations often coexist with gastrointestinal cancers [ 11 , 17 ]. The association of GIST with secondary tumors ranges from 4.5% to 33% in different series (average, 13%) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This rate was reported to be 21% in a retrospective monocentric analysis by Comandini et al [ 19 ]. Although varying rates have been reported in literature, the association of GISTs with secondary tumors was reported to be 20% in a meta-analysis performed in 2019 [ 11 , 12 ]. Most studies have shown that GISTs are most commonly associated with gastrointestinal and genitourinary system tumors [ 11 , 12 , 14 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%